Antioxidant Capacity of Free Volatile Compounds from Olea europaea L. cv. Oblica Leaves Depending on the Vegetation Stage - Renata Jurišić Grubešić (MDPI AG, 2021)
Previous research on specialized metabolites of olive leaves has focused on the phenolic components and their biological role. The research in this article focuses on the metabolites that form free volatile compounds (FVCs). The composition of FVCs is divided into compounds isolated in the oil phase (essential oils; EO) and in the aqueous phase (hydrosols; Hy) from leaves of Olea europaea L. cultivar Oblica. Plant material was collected from the same olive tree over a six-month period, from December to May, and analyzed by gas chromatography–mass spectrometry (GC–MS). The compounds β-caryophyllene, α-humulene, allo-aromadendrene, docosane, hexadecanoic acid and oleic acid were identified in all EO study periods. In the Hy in all studied periods, the major compounds are α-pinene, β-ionone, myristicin, docosane, 1-hexanol, oleic acid and (E)-β-damascenone. The differences in the qualitative composition of FVC are directly related to the phenological development of the leaves. Antioxidant capacity of the EOs and hydrosols was measured with two methods, ORAC and DPPH. Hydrosol extracts showed higher capacity than the EOs in all methods.